Dormancy in promising clones and potato varieties, under conditions of the Trujillo state (Agroindustria, Sociedad y Ambiente, 2024)
The potato crop is an annual herbaceous plant, it belongs to the Solanaceae family that produces tubers. In order to evaluate the time at which dormancy ends and the characteristics of turnip tops in potato tubers harvested in the La Cristalina Trujillo Experimental Field, located at 2718 meters above sea level, with an average temperature of 18.15ºC and relative humidity of 76 %, a test was carried out on recently harvested tubers located in the seed storage shed, the experimental design used was completely randomized with 10 repetitions and 50 seeds for each material or treatment. The potato varieties used were Sabanitaina, Dalinia and Tibisay and the promising clones 399101-1; 391047-34 and 397079-6 from the International Potato Center (CIP). The variables evaluated were the time at which grelation began or the end of dormancy; the percentage of sprouting, the number, color, shape and length of the turnip greens, the shape of the growth of the apex of the turnip greens. The onset of grelation in all materials occurred at 90 days. The sprouting percentage was higher in clone 397079-6. In the Tibisay variety and clone 397079-6, a greater number of turnip greens per tuber was evident (5 turnip greens on average). The greatest lengths of turnip greens were observed in Sabanitainia. Regarding the color of the turnip greens, it was evident that they varied between pink, purple and greenish white; The shape of the apex growth, for most materials, was intermediate.
Keywords: olanum tuberosum, turnip greens, sprouting, dormancy